Knowledge, perception, and experience of adult population toward traditional and complementary medicine (TCM) in Puncak Alam, Selangor / Muhammad Amsyar Azhar, Noor Fadzlin Ashikin Abd Rahman and Nur Amalina Fakhruddin - Azhar, Muhammad Amsyar; Abd Rahman, Noor Fadzlin Ashikin; Fakhruddin, Nur Amalina (2016)
Traditional and complementary (TCM) is a combination of traditional medicine and complementary medicine which enclosed products, practices and practitioners. The usage of traditional and complementary medicine (TCM) in Malaysia is widely and conveniently practiced without consultation with healthcare professional. Its can lead to serious side effect when combine it with modern medicine. Objectives: The study was conducted to assess perceptions, knowledge and experience of adult population towards traditional and complementary medicine (TCM) in Puncak Alam, Selangor.